2016
DOI: 10.1111/1467-8578.12151
|View full text |Cite
|
Sign up to set email alerts
|

‘When words don't come easily’: personal narratives from adolescents experiencing shyness as an emotional and behavioural problem in the school context

Abstract: The purpose of this article is to present narratives from 15 adolescents experiencing shy behaviour as an emotional and behavioural problem in the school context in light of narrative understanding. The investigation is intended to generate knowledge about this largely underresearched phenomenon based on the personal accounts of those who are actually experiencing it. Their narratives are the foundation for a discussion regarding implications for future practice in the context of school in relation to this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…We have employed the cultural-historical emphasis on learning and development as outcomes of a dialectic between individual and cultural practices relatively lightly, preferring to focus on how these views are reflected in the emphases that both Lund (2012Lund ( , 2016 and Scott (2006) place on how shyness arises in interactions, in this case between learners and school practices. These views are also evident among others who have taken a primarily traitbased view of shyness (Coplan et al, 2020;Crozier, 2020) and offer teachers a way of seeing how their actions can assist shy children and ensure they are included in the flow of classroom and school life.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have employed the cultural-historical emphasis on learning and development as outcomes of a dialectic between individual and cultural practices relatively lightly, preferring to focus on how these views are reflected in the emphases that both Lund (2012Lund ( , 2016 and Scott (2006) place on how shyness arises in interactions, in this case between learners and school practices. These views are also evident among others who have taken a primarily traitbased view of shyness (Coplan et al, 2020;Crozier, 2020) and offer teachers a way of seeing how their actions can assist shy children and ensure they are included in the flow of classroom and school life.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…When, how, and for whom shyness is problematic, has to be seen as an interaction between the subjective experiences of an individual student, and the demands of the context 4 (Lund, 2016). According to this view, although shyness can be an individual trait, it is also a result of transactional processes over time, including parenting, school environment and relationships with peers.…”
Section: Introductionmentioning
confidence: 99%
“…Although these behaviors are not necessarily problematic in themselves, Nilsen (2018) found that teachers experienced withdrawn and shy children to be struggling both socially and academically, an argument substantiated in international research (Hughes & Coplan, 2010;Hymel et al, 1990). The threshold for when shyness is problematic and when it is not, and for whom, have to be seen in interaction between the subjective experiences of the individual, and the demands of the context (Lund, 2016). Importantly, childhood shyness may also lead to later difficulties, especially lower selfesteem, anxiety, loneliness, and fewer positive coping strategies (Findlay et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no agreed definition of shyness as a potential behavioral and emotional problem (Lund, 2016), it is commonly defined by psychologists as "wariness in the face of social novelty and/ or self-conscious behavior in situations of perceived social evaluation" (Coplan & Rubin, 2010, p. 9). The behaviors displayed can be quiet, withdrawn, anxious and inhibited (Mjelve et al, 2019).…”
Section: Introductionmentioning
confidence: 99%